Survey on frontiers of language and robotics. (18th August 2019) - Tangiuchi, T.; Mochihashi, D.; Nagai, T.; Uchida, S.; Inoue, N.; Kobayashi, I.; Nakamura, T.; Hagiwara, Y.; Iwahashi, N.; Inamura, T.
ABSTRACT: The understanding and acquisition of a language in a real-world environment is an important task for future robotics services. Natural language processing and cognitive robotics have both been focusing on the problem for decades using machine learning. However, many problems remain unsolved despite significant progress in machine learning (such as deep learning and probabilistic generative models) during the past decade. The remaining problems have not been systematically surveyed and organized, as most of them are highly interdisciplinary challenges for language and robotics. This study conducts a survey on the frontier of the intersection of the research fields of language and robotics, ranging from logic probabilistic programming to designing a competition to evaluate language understanding systems. We focus on cognitive developmental robots that can learn a language from interaction with their environment and unsupervised learning methods that enable robots to learn a language without hand-crafted training data. GRAPHICAL ABSTRACT: